Analisis Kerusakan Mesin CNC Milling Menggunakan Metode Fault Tree Analysis (FTA) Dan Failure Mode And Effect Analysis (FMEA) (Studi Kasus Mesin CNC Milling Di Lab. Jurusan Teknik Mesin, Universitas Riau) - Saputra, Rio Agus; Susilawati, Anita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The CNC machines are computer-controlled machines using numeric codes, symbols and letters as command data. A CNC Milling machine at the Mechanical Engineering Laboratory of the University of Riau has damaged and disrupted engine performance. The purpose of this study is to determine the types of damage, causes, and efforts and suggestions of actions that can be done to improve engine performance for CNC milling in Riau University Laboratory. The method is used in this research of the Fault Tree Analysis (FTA) method which is used to find the caused of the damage to the basic event and Failure Mode and Effect Analysis (FMEA) that is used to search priority problem through Risk Priority Number (RPN). The result showed damaged of components such as pneumatic cylinders of protective door, ATC pneumatic brauer units, pneumatic valves and saddle. The result of critical component analysis of leakage on pneumatic valve component was the most critical risk with RPN of 448. The actions to reduce the highest of RPN were repairing, prevention and maintenance on the CNC milling machine. Proposed repair was the replacement of components that have been damaged and optimize the precautions and maintenance in accordance with the instructions in the manual book.Keyword: FTA, FMEA, RPN, CNC Milling machine